In vivo effects of eltrombopag on platelet function in immune thrombocytopenia: no evidence of platelet activation - Psaila, Bethan (American Society of Hematology, 2012)
The effects of eltrombopag, a thrombopoietin-receptor agonist, on platelet function in immune thrombocytopenia (ITP) are not fully characterized. This study used whole blood flow cytometry to examine platelet function in 20 patients receiving eltrombopag treatment at days 0, 7, and 28. Platelet surface expression of activated GPIIb/IIIa, P-selectin, and GPIb was measured with and without low and high adenosine diphosphate (ADP) and thrombin receptor activating peptide (TRAP) concentrations. Before eltrombopag treatment with no ex vivo agonist, platelet activation was higher in ITP patients than controls. Platelet GPIb and activated GPIIb/IIIa expression without added agonist was unchanged following eltrombopag treatment, whereas a slight increase in P-selectin was observed. Expression of P-selectin and activated GPIIb/IIIa in response to high-dose ADP was lower during eltrombopag treatment than at baseline. Eltrombopag led to a slight increase in platelet reactivity to TRAP only in responders to eltrombopag but not to levels above those in controls; whole blood experiments demonstrated that this increase was probably because of higher platelet counts rather than higher platelet reactivity. In conclusion, although thrombocytopenic ITP patients have higher baseline platelet activation than controls, eltrombopag did not cause platelet activation or hyper-reactivity, irrespective of whether the platelet count increased.